Adverse Events Related to SARS-Cov-2 Vaccination: A Systematic Review and Meta-Analysis - Segun Bello; David Taiwo Ajayi; Akinmade Adepoju; Temitope Omotosho; Rotimi Felix Afolabi; Babatunde Gbadebo; Mobolaji Modinat Salawu; Eniola Adetola Bamgboye; Olabisi Oduwole; Adeniyi Fagbamigbe; Ayo Stephen Adebowale (Masters Program in Public Health, 2023)
Background: Vaccination has been adopted as a key public health strategy for combating the COVID-19 pandemic. The accelerated SARS-CoV-2 vaccines’ development had limited time for extensive investigation of the adverse events. The study aimed to assess the average adverse events rates in published COVID-19 vaccination studies. Subjects and Method: The study used systematic review and meta-analysis involving studies that reported adverse events following administration of any of the approved COVID-19 vaccines in humans. A highly specific search strategy was developed and implemented in PubMed. The core search string was “(COVID-19 OR COVID OR